2019
DOI: 10.3389/fneur.2019.00138
|View full text |Cite
|
Sign up to set email alerts
|

Management of Blood Pressure During and After Recanalization Therapy for Acute Ischemic Stroke

Abstract: Ischemic stroke is a common neurologic condition and can lead to significant long term disability and death. Observational studies have demonstrated worse outcomes in patients presenting with the extremes of blood pressure as well as with hemodynamic variability. Despite these associations, optimal hemodynamic management in the immediate period of ischemic stroke remains an unresolved issue, particularly in the modern era of revascularization therapies. While guidelines exist for BP thresholds during and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 131 publications
(174 reference statements)
0
62
0
2
Order By: Relevance
“…As for the correlation of lnc-MALAT1 with disease severity and inflammation in neurological and cerebrovascular disease patients, only one study shows that elevated lnc-MALAT1 expression is correlated with less advanced lesions in atherosclerosis patients ( 12 ). Considering that lnc-MALAT1 might participate in the cerebrovascular pathologies of stroke according to previous studies, and it presented an anti-inflammatory effect in cardiovascular and cerebrovascular diseases, we hypothesized that lnc-MALAT1 expression might be related to disease risk, progression, or inflammation level of AIS ( 9 12 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the correlation of lnc-MALAT1 with disease severity and inflammation in neurological and cerebrovascular disease patients, only one study shows that elevated lnc-MALAT1 expression is correlated with less advanced lesions in atherosclerosis patients ( 12 ). Considering that lnc-MALAT1 might participate in the cerebrovascular pathologies of stroke according to previous studies, and it presented an anti-inflammatory effect in cardiovascular and cerebrovascular diseases, we hypothesized that lnc-MALAT1 expression might be related to disease risk, progression, or inflammation level of AIS ( 9 12 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme variation of BP is very common in patients with AIS who are eligible for MT, and is partly explained by a deficient BP auto-regulation within the ischemic injury 15 22 23. Such an elevated BP, although often described as a risk factor for symptomatic intracranial hemorrhage, worse outcomes and mortality, may also be considered as a marker of stroke severity as well and serve as a compensatory mechanism to maintain cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these uncertainties, BP management in the acute phase of ischemic stroke remains an unresolved and controversial issue, especially in the era of EVT. 10 There is insufficient information on the relationship between BP and the probability of successful reperfusion after EVT. A previous study showed that the benefit of EVT is consistent across the entire range of SBP.…”
mentioning
confidence: 99%